2014
DOI: 10.1016/j.nuclphysa.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly rotating neutron stars in the global and local charge neutrality cases

Abstract: In our previous treatment of neutron stars, we have developed the model fulfilling global and not local charge neutrality. In order to implement such a model, we have shown the essential role by the Thomas-Fermi equations, duly generalized to the case of electromagnetic field equations in a general relativistic framework, forming a coupled system of equations that we have denominated Einstein-Maxwell-Thomas-Fermi (EMTF) equations. From the microphysical point of view, the weak interactions are accounted for by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 33 publications
(73 reference statements)
2
69
0
Order By: Relevance
“…For the rotational periods as the ones observed in SGR/AXPs (P ∼ 2-12 s), the structure of the rotating NS can be accurately described by small rotation perturbations from the spherically symmetric configuration (see, e.g., Belvedere et al 2014Belvedere et al , 2015, using the Hartle's formalism (Hartle 1967 charge neutrality are shown in Fig. 2.…”
Section: Mass-radius Relation and Moment Of Inertiamentioning
confidence: 85%
See 1 more Smart Citation
“…For the rotational periods as the ones observed in SGR/AXPs (P ∼ 2-12 s), the structure of the rotating NS can be accurately described by small rotation perturbations from the spherically symmetric configuration (see, e.g., Belvedere et al 2014Belvedere et al , 2015, using the Hartle's formalism (Hartle 1967 charge neutrality are shown in Fig. 2.…”
Section: Mass-radius Relation and Moment Of Inertiamentioning
confidence: 85%
“…mass and radius, we need to construct the equilibrium configurations of a uniformly rotating NS in the range of the observed periods. We have shown in Rotondo et al (2011);Rueda et al (2011);Belvedere et al (2012Belvedere et al ( , 2014 that, in the case of both static and rotating NSs, the Tolman-Oppenheimer-Volkoff (TOV) system of equations (Oppenheimer & Volkoff 1939;Tolman 1939) is superseded by the Einstein-Maxwell system of equations coupled to the general relativistic Thomas-Fermi equations of equilibrium, giving rise to what we have called the Einstein-Maxwell-Thomas-Fermi (EMTF) equations. In the TOV-like approach, the condition of local charge neutrality is applied to each point of the configuration, while in the EMTF equations the condition of global charge neutrality is imposed.…”
Section: Neutron Star Structurementioning
confidence: 99%
“…The extension of the above formulation to the case of uniform rotation has been recently achieved in (Belvedere et al 2014) within the Hartle formalism (Hartle 1967). It is worth TABLE 1 Properties of the high-magnetic field pulsars obtained assuming fiducial neutron star parameters, R = 10 km and I = 10 45 g cm 2 , respectively, and using Eq.…”
Section: Neutron Star Structurementioning
confidence: 99%
“…to underline that the influence of the induced magnetic field owing to the rotation of the charged core of the neutron star in the globally neutral case is negligible as we will show in subsection 2.1. From the integration of the equations of equilibrium, we computed in Belvedere et al (2014), for different central densities ρ c and circular angular velocities Ω, the mass M, polar R p and equatorial R eq radii, angular momentum J, eccentricity ǫ, moment of inertia I, as well as quadrupole moment Q of the configurations. The angular momentum J of the star is given by…”
Section: Neutron Star Structurementioning
confidence: 99%
See 1 more Smart Citation